Understanding the phase formation and compositions of barium carbonate modified NiO-yttria stabilized zirconia for fuel cell applications. (7th December 2015) - Wang, Zhihong; Liu, Mingfei; Li, Xiaxi; Blinn, Kevin; Lai, Samson; Lü, Zhe; Liu, Meilin
Abstract: A simple modification of a conventional nickel-yttria stabilized zirconia (Ni-YSZ) anode for a solid oxide fuel cell (SOFC) by BaCO3 can enhance the coking resistance of the anode in carbon-containing fuels. In this study, X-ray diffraction, Raman spectroscopy, and thermo-gravimetric analysis are used to investigate the chemical reactions among BaCO3, NiO, and YSZ to understand the phase formation and compositions during fabrication process. Our results indicate that BaCO3 reacts readily with YSZ to produce a BaZr1−x Yx O3−δ (BZY) phase at temperatures higher than 900 °C. For the mixture of BaCO3 and NiO, both BaNiO3 and BaNiO2.36 are formed at 900 °C, which are unstable at elevated temperatures, in the presence of YSZ, or under a reducing atmosphere. The results imply that a BZY/YSZ-BaO/Ni anode can be easily created by a simple heat-treatment (e.g., during cell fabrication) and a subsequent reducing process (e.g., exposure to the fuel) of a mixture consisting of BaCO3, NiO, and YSZ. Highlights: BaCO3 reacts with YSZ to produce a BaZr1−x Yx O3−δ (BZY) phase. BaCO3 reacts easily with NiO to form a mixture of BaNiO3 -BaNiO2.36 at 900 °C. The BaNiO3 -BaNiO2 phases are unstable at elevated temperatures or under a reducing atmosphere.